Design and analysis of a fair, efficient and stable multi-server adaptive streaming protocol. (October 2021) - Zhang, Shengkai; Liu, Gaoyang; Xu, Ji; Wan, Shaohua
Abstract: Due to the surging bandwidth demand for applications like 360 ° video streaming, hypertext transfer protocol (HTTP) adaptive video streaming has been extended to fetch contents from a single server to multiple servers. However, when players share a bottleneck link, it fails to hold three critical properties: fairness, efficiency, and stability . Effective algorithms have been proposed to tackle the problem in the single-server case. We revisit the three properties and show that they degenerate in multi-server streaming. In this paper, we propose MultiFast, a protocol that offers the best user experience by achieving fair, efficient, and stable multi-server video streaming. MultiFast consists of (1) a bitrate selection algorithm that ensures fairness with concurrent connections; (2) a connection management algorithm that ensures efficiency and stability by managing connections based on network conditions. Our real-world experiments show that MultiFast achieves the best performance in fairness, efficiency, and stability metrics, outperforming its closest alternative. Graphical abstract: Highlights: A comprehensive bitrate selection algorithm achieves fairness. A connection management algorithm achieves efficiency and stability simultaneously. An in-depth theoretical analysis guarantees the correctness of our design. Real-world experiments demonstrate the effectiveness.